(untitled) (Research, Society and Development, 2021)
This study intends to describe the sociodemographic profile of attendees of a Psychosocial Care Center III, in the city of Sao Paulo, who needed the user embracement as a care strategy in the period of time between november of 2012 and december of 2016. This is an explorative descritive study of documental analysis with quantitative approach. The user embracement’s document and the medical registers were analysed. The data analysis was done with the Software Statistical Package for the Social Sciences (SPSS), Versão 20. It was verified that the majority of attendees was woman, white skined, studies until high school, age between 31 and 59, receiving social benefit and the main diagnosis was schizophrenia. This study helped to share information about the user embracement, which is an important care strategy still insufficiently studied.